Korelasi Pengetahuan Anemi dan Konsumsi Gizi Seimbang dengan Kejadian Anemia pada Remaja Putri - Marsa Syifa Khaila; Gianita Yulia Lestari; ⁠Adila Nurhadiya; ⁠⁠Mia Miranda; Dita Septiani (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Anemia remains a global health problem. At SMK Sultah Baruna, 6,9% of adolescent girls were found to have anemia. The causes of anemia in adolescents include inadequate intake of balanced nutrition, bleeding, and worm infections. Lack of knowledge about anemia can influence adolescent’s behaviour in consuming balanced nutritional foods. This study is to determine the relationship between anemia knowledge and balanced nutrition behavior with the incidence of anemia in students of SMK Sulthan Baruna Cidaun. This study used a quantitative design with a quasi-experimental approach. The population consisted of 62 adolescent girls, divided into two groups: 31 with anemia and 31 without anemia. Accidental sampling was used. The research instruments included a knowledge questionnaire and a 24-hour food recall form. Data were analyzed using the dependent t-test (paired t-test). Based on research result 87.1% did not consume balanced nutritional foods. Statistical analysis showed a significant relationship between knowledge and balanced nutritional consumption (p < 0.016). Lack of knowledge and unbalanced food consumption behavior are risk factors for anemia in adolescents.